We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
177
1
avatar+484 

 

 Dec 10, 2018
 #1
avatar+103913 
+2

( f + g) (x)  = 

 

 f(x) + g(x) =

 

[ x^3 - x ] + [ x^3 + 2x^2 - 10 ]  =

 

2x^3 + 2x^2 - x - 10

 

 

( f - g) (x) =

 

f(x) - g(x)   =

 

[ x^3 - 2x^2  + 12x - 6 ] - [ 4x^2 - 6x + 4 ]  =

 

x^3 - 6x^2 + 18x - 10

 

 

 

( f * g)(x)  =

 

f(x) * g(x) =

 

[x^2 + 2x - 6 ] * [ x^4  + 3 ]   =     

 

x^6 + 2x^5  - 6x^4 + 3x^2 + 6x - 18  

 

 

 

cool cool cool

 Dec 10, 2018

8 Online Users

avatar